Estimation on the Underwater Explosion Equivalent Based on the Threshold Monitoring Technique - Yan Wang; Xiaoming Wang; Zhehan Liu; Wei Tang; Jian Li; De Nan; Shiya Zou (Shock and Vibration)
Underwater nuclear explosions can be monitored in near real-time by the hydroacoustic network of the International Monitoring System (IMS) established by the Comprehensive Nuclear-Test-Ban Treaty (CTBT), which could also be used to monitor underground and atmospheric nuclear explosions. The equivalent is an important parameter for the nuclear explosions’ monitoring. The traditional equivalent estimation method is to calculate the bubble pulsation period, which is difficult to obtain satisfactory results under the current conditions. In this paper, based on the passive sonar equation and the conversion process of acoustic energy parameters in the hydroacoustic station, the threshold monitoring technique used for underwater explosion equivalent estimation was studied, which was not limited to the measurement conditions and calculation results of the bubble pulsation period. Through the analysis of practical monitoring data, estimation on the underwater explosion equivalent based on the threshold monitoring technique was verified to be able to reach the accuracy upper boundary of current methods and expand the measurement range to further ocean space, along with the real-time monitoring capability of IMS hydroacoustic stations which could be estimated by this method.